THE ROLE AND PROBLEMS OF TRANSLATION IN THE INTERNATIONAL BANKING SYSTEM - Meliyeva , Nargizaxon; Abduvaliyeva , Mushtariy (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This article examines the theoretical and practical significance of translation in the international banking system. It argues that the effectiveness of interbank communication in the context of global financial integration directly depends on the quality of translation. The study explores the complexity of financial terminology, linguistic and cultural differences, as well as the capabilities and limitations of automated translation tools. Scientific and practical recommendations for addressing these challenges are proposed.